2012
DOI: 10.1073/pnas.1211845109
|View full text |Cite
|
Sign up to set email alerts
|

Testis tissue explantation cures spermatogenic failure in c-Kit ligand mutant mice

Abstract: Male infertility is most commonly caused by spermatogenic defects or insufficiencies, the majority of which are as yet cureless. Recently, we succeeded in cultivating mouse testicular tissues for producing fertile sperm from spermatogonial stem cells. Here, we show that one of the most severe types of spermatogenic defect mutant can be treated by the culture method without any genetic manipulations. The Sl/Sl d mouse is used as a model of such male infertility. The testis of the Sl/Sl d mouse has only primitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…The kit ligand (KITL), a cytokine type of growth factor, is produced by Sertoli cells in the testis and must interact with the kit receptor found on differentiating spermatogonia and spermatocytes for spermatogenesis to be completed (7,8). These authors report that the addition of recombinant KITL and colony stimulating factor-1 (CSF-1) to the medium of organ cultures of testis tissue derived from mice deficient in the production of KITL induced spermatogenesis to proceed through meiosis (6). The efficiency of male gamete production in these organ cultures, and in all the earlier studies described here, is very low.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…The kit ligand (KITL), a cytokine type of growth factor, is produced by Sertoli cells in the testis and must interact with the kit receptor found on differentiating spermatogonia and spermatocytes for spermatogenesis to be completed (7,8). These authors report that the addition of recombinant KITL and colony stimulating factor-1 (CSF-1) to the medium of organ cultures of testis tissue derived from mice deficient in the production of KITL induced spermatogenesis to proceed through meiosis (6). The efficiency of male gamete production in these organ cultures, and in all the earlier studies described here, is very low.…”
mentioning
confidence: 87%
“…This technique was further extended when it was demonstrated that spermatogonia grown in culture in the absence of somatic cells could be transplanted into recipient testes and proceed through meiosis to form reproductively functional haploid gametes (5). Sato et al now expand their observations again by showing that their system can be used to correct spermatogenic defects in vitro (6). The kit ligand (KITL), a cytokine type of growth factor, is produced by Sertoli cells in the testis and must interact with the kit receptor found on differentiating spermatogonia and spermatocytes for spermatogenesis to be completed (7,8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of genetic disorders, one possible treatment strategy has been proposed based on experimental evidence. Namely, Sato and coworkers succeeded in restoring spermatogenesis in Sl/Sl d mutant testes bearing mutations in genes encoding SCF by culturing with recombinant SCF (Sato et al 2012). This strategy would be particularly effective in cases in which the mutation is in a gene encoding a somatic factor and/or soluble factor, because such defects can be compensated by simply adding the recombinant protein to the medium (Fig.…”
Section: Proof Onlymentioning
confidence: 99%